Biochemical Indicators of Endometrial Receptivity in Uterine Function - Manal Abdulmunem Ibrahim (Indonesian Journal on Health Science and Medicine, 2026)
Background: Endometrial receptivity is a critical prerequisite for successful embryo implantation and pregnancy, involving complex molecular interactions within the uterus. Specific Background: Implantation failure remains a major cause of infertility and recurrent implantation failure, despite advances in assisted reproductive technologies. Numerous biomolecules, including genes, proteins, microRNAs, extracellular vesicles, hormones, immune mediators, and microbial-related factors, have been investigated as indicators of uterine receptivity. Knowledge Gap: Although many biomarkers have been reported, comprehensive synthesis of recent evidence regarding biochemical indicators associated with receptive and non-receptive endometrium remains limited. Aims: This review aimed to summarize contemporary evidence regarding biomolecules associated with endometrial receptivity and implantation success. Results: Analysis of studies published between 2019 and 2023 identified multiple biomarkers linked to receptive endometrium, including HOXA10, LIF, CTNNA2, annexins, integrins, mucins, osteopontin, CD44, IGFBP-7, CK7, extracellular vesicle-associated microRNAs, CD63, and progesterone-related pathways. In contrast, implantation failure was associated with reduced HSD17B2, AZGP1, TPPP3, S100A13, estrogen receptor β, progesterone receptors, and progesterone levels, alongside dysregulated immune profiles, altered microRNA expression, elevated CD9, oxidative stress, microbial disturbances, mitochondrial dysfunction, and cellular senescence. Novelty: This review integrates recent findings on genetic, proteomic, transcriptomic, immunological, hormonal, and extracellular vesicle-derived biomarkers relevant to endometrial receptivity. Implications: Identification and characterization of these biomarkers may support minimally invasive assessment of uterine receptivity, improve implantation prediction, and facilitate personalized management strategies for infertility and recurrent implantation failure. Keywords: Endometrial Receptivity, Embryo Implantation, Recurrent Implantation Failure, Extracellular Vesicles, Biomarkers Key Findings Highlights Multiple genes, proteins, and extracellular vesicle contents were associated with successful implantation. Recurrent implantation failure was characterized by molecular, immune, hormonal, and metabolic dysregulation. Minimally invasive uterine fluid analysis provides promising approaches for receptivity assessment.